Public policy coverage and access to medicines in Brazil - Ricardo Montes de Moraes; Maria Angelica Borges dos Santos; Fabiola Sulpino Vieira; Rosimary Terezinha de Almeida (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE Describe consumption patterns for monetary and non-monetary acquisition of medicines according to age and income groups, highlighting pharmaceuticals associated with health programs with specific access guarantees. METHODS Descriptive observational study using microdata from the 2017-2018 Pesquisa de Orçamentos Familiares (Household Budget Survey, POF/IBGE). We initially reviewed programs/policies with specific guarantees of access to medicines in the SUS. Using the pharmaceutical product list of POF-4 (chart 29 of the questionnaire on individual expenditures), we selected the medicines related to these programs. We then described frequencies and percentages for not reporting medicine consumption and for reporting consumption (either through monetary or non-monetary acquisition) according to age and income groups. For medicines with distinctive access guarantees, we compared average monthly values of acquisitions and consumption patterns by age and income. RESULTS 63% of those in the ≤ 2 minimum wage (MW) household income group did not report consuming medicines in the last month. Among those earning > 25 MW, 44.3% did not report consumption. Non-monetary acquisitions of medicines were mainly reported for the < 10 MW group and for the elderly and accounted for 20.5% of the total consumption of medicines (in value). For policies with specific access guarantees, non-monetary acquisitions reached 33.6% of total consumption. This percentage varied for the various selected medicines: vaccines, 83.3%; cancer drugs, 70.3%; diabetes, 47.9%; hypertension, 35.9%; asthma and bronchitis, 29.2%; eye problems, 14%; prostate and urinary tract, 10.7%; gynecological, 11.6%; and contraceptives, 9.7%. CONCLUSION Shares for non-monetary acquisitions of medicines are still low but benefit mainly lower-income and older age groups. Policies and programs with specific access guarantees to medicines have increased access. Results suggest the need to strengthen and expand pharmaceutical care policies.